Laparoscopic vs Open Appendectomy : A Comparative Study - Islam, Sardar Rezaul; Pasha, Kamal; Rahman, Shahinur; Nasir, Emdad; Hanif, Emon; Barman, Auditi (Bangladesh Journal of Endosurgery, 2014)
Backgraound: Open appendectomy (OA) has been the treatment of choice for acute appendicitis since its introduction by Mc-burney in 1884. Laparoscopic appendectomy(LA) though widely practiced, has not gained universal approval. LA was first described in 1983. Some early studies showed equivocal results about benefit of LA. Recent studies showed overall benefit in favour of LA. So far no such a large study was done in any Bangladeshi hospital. So, we decided to do this study with a view to evaluate the therapeutic benefit of LA by comparing with conventional OA. Materials and methods: We collected data of 763 appendectomies done in Jahurul Islam medical college hospital from July 2007 to June 2012 for a period of 5 years. Out of them 448 had conventional OA and 315 had LA. We compared the mean operation time, time of first oral feeding, narcotic analgesic requirement, duration of post operative hospital stay. Results: We found that mean operation time was 33±5.8 minute and 37± 7.5 minute in LA and OA respectively. Duration of post operative hospital stay was 1.2 days shorter in Laparoscopic group. LA required 1.1 shots of less analgesic than OA. Oral feeding was resumed 21 hours earlier following LA compared to OA. Laparoscpic appendectomy was safely performed in paediatric patient without any adverse effect. We also found that, in female patient, concurrent ovarian cysts, tubal pregnancy and endometriosis can be diagnosed and managed laparoscopically in the same sitting. Conclusion: Our study found that laparoscopic appendectomy is an effective and safe procedure irrespective of age and sex of the patient. LA has added advantage of early return of bowel movement, less post-op hospital stay and less requirement of narcotic analgesic.